Peran Asesmen Bimbingan Dan Konseling Dalam Menunjang Keberhasilan Pendidikan Peserta Didik - Amirah, Nadiratul; Nurfarhanah, Nurfarhanah; Ardi, Zadrian (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Assessment in guidance and counseling is an important component that functions as a basis for planning, implementing and evaluating guidance and counseling services. Comprehensive assessments enable counselors/BK teachers to understand the characteristics of students in depth, including academic, social, emotional and personal aspects. This article describes the important role of guidance and counseling assessments in supporting the success of student education through mapping needs, identifying potential and problems and making appropriate service decisions. This study is supported by theory, research and practice that show that effective assessments contribute directly to the optimal development of students in schools.